MEANING OF IMMUNIZATION BY PNEUMO 23 AND ACT HIB IN THE PREVENTION OF THE RECURRENT RESPIRATORY DISEASES AMONG CHILDREN FROM THE CLOSED CHILDREN'S FACILITIES - S.V. Budalina; S.A. Tsar'kova; V.P. Shilova (Union of pediatricians of Russia, 2007)
The researchers performed a comparative evaluation of the clinical and microbiological efficacy of the pneumo 23, ACT HIB and Grippol vaccine combination for the prevention of the recurrent respiratory diseases among children from the closed children's facilities if compared with mono immunization by Grippol. The open research included 60 children (average age was 3,33 ± 0,21 years) with recurrent respiratory diseases. Depending on the results of the microbiological examination, the children were divided into 2 groups. The 1st group consisted of 35 children with negative bacteriological result, while the 2nd group consisted of the haemophilus influenzae and pneumococcus carriers. The children from the 1st group were divided into 2 subgroups: the 1st subgroup included 13 children vaccinated with pneumo 23 and Grippol, 22 children from the 2nd subgroup were immunized with Grippol only. 15 patients from the 2nd group were immunized against flu, pneumococcus and hemophilic infections (1st subgroup); while the 2nd subgroup (n = 10) was composed of children vaccinated with Grippol only. The carrier level was evaluated in dynamics in 1 and 6 months accordingly. the number of the acute respiratory diseases, their structure, the number of antibiotic courses and disease duration - in 12 months, immune status - in 6 months after immunization. Within the general sample, the carrier level made up 36,7% with the prevailing capsular variant of h. influenzae b type. The share of h. influenzae b carriers reduced by 2,5 times to make up 6,7% after immunization with 3 vaccines. Children vaccinated with Grippol only showed no reliable differences with regards to the discharge of haemophilus influenzae before and after vaccination in the observation dynamics. Vaccination against flu contributed to reduction of pneumonia sickness rate by 3 times, pharyngitis sickness rate by 2 times, laryngotracheitis sickness rate by 2,3 times, while the total number of the acute respiratory diseases remained the same. Thus, they showed that vaccination with Grippol only may not be sufficient to reduce the frequency of recurrent episodes of the acute respiratory diseases among sickly children. bacteriologically positive children must be vaccinated with three vaccines, which leads to reduction of the total number of the acute respiratory diseases by 4,6 times and reduces rhino pharyngitis sick ness rate by 2 times, pharynxgitis sickness rate by 8 times, otitis sickness rate by 6 times, bronchitis sickness rate by 4,3 times and pneumonia sickness rate by 3 times. for children, who have negative results of the microbiological examination, vaccination with Grippol should be combined with pneumo 23, which reduces the total number of the acute respiratory diseases by 6,5 times, rhinopharyngitis sickness rate by 5 times, pharyngitis sickness rate by 8,7 times, otitis sickness rate by 7 times, bronchitis sickness rate by 5 times and pneumonia sickness rate by 7 times. Combined immunization (pneumo 23, ACT HIB and Grippol) to prevent recurrent respiratory diseases among preschool children is safe and has positive clinical and microbiological effects.Key words: sickly children, closed specialized children's facilities, immunization.